Allelic diversification at the class II DQB locus of the mammalian major histocompatibility complex. - Gyllensten, U B (1990)
The allelic diversity at HLA class II loci either arose after the divergence of hominoid lineages or, alternatively, the polymorphism was present before speciation and has been maintained by selection. Here, we report the use of oligonucleotide primers to amplify, by the polymerase chain reaction, and sequence the polymorphic second exon of the DQB locus from 11 species, spanning more than 40 million years of mammalian evolution. Phylogenetic analysis reveals that of the four human DQB allelic types (DQB1-B4), three (DQB1-3) were found in chimpanzee and gorilla and two (DQB3 and -4) were identified in the rhesus monkey, suggesting that some of these types are 5-20 million years old. The ratio of replacement to silent substitutions was calculated between members of the same allelic type from different species. These results suggest that the evolution of the DQB3 allelic type is more constrained than that of the DQB1 allelic type; both evolve more slowly than the DXB locus, a linked but presumably nonexpressed locus. Further, the clustering of allelic subtypes by species in the phylogenetic tree indicates that allelic diversification has occurred subsequent to the divergence of hominoids. Finally, some haplotype combinations of DQA and DQB alleles are common to several hominoid species and may have been maintained for at least 5 million years.